Analisis Efektivitas Pengelolaan Dana Desa Terhadap Pembangunan Infrastruktrur Desa Gapluk - Triana Belucci; Lis Setyowati; Waloyo Waloyo (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the effectiveness of village fund management in Gapluk Village infrastructure development. The research method used is a qualitative method. Data collection techniques used are documentation techniques, interviews and observation. The data analysis technique used is a qualitative descriptive analysis technique. The results of this study are that all processes of managing village funds in the development of village funds in Gapluk Village starting from the planning, management to monitoring stages have been running effectively because the implementation is in accordance with applicable regulations and involves the local community in every stage of village fund management.